Content Vol. 43 No. 1 (2022) - Editorial, Coordinador (Revista Mexicana de Ingenieria Biomedica, 2022)
E-book edition of the volume 43, number 1, year 2022, of the Revista Mexicana de Ingeniería Biomédica. In this issue: Detection of COVID-19 Lung Lesions in Computed Tomography Images Using Deep Learning Healing of Wounds Treated with Chitosan Hydrogels with Extracts from Aloe vera and Calendula officinalis A Chitosan-based Hydrogel with PLCL, ZnO NPs, and Oligoelements: A Promising Antibiotic Scaffold for Tissue Engineering Effect of the Unilateral Breast Cancer Surgery on the Shoulder Movement: Electromyographic and Motion Analysis Biomechanics Assessment of Kinematic Parameters of Low-Sprint Start in High-Performance Athletes Using Three Dimensional Motion Capture System